2015
DOI: 10.21548/36-1-937
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Using Entomopathogenic Nematodes to Control the Vine Mealybug, Planococcus ficus, in South African Vineyards

Abstract: In South Africa, the most common method of mealybug control has been the use of chemical insecticides. Entomopathogenic nematodes (EPNs) of the of the families Heterorhabditidae and Steinernematidae potentially can be used within an integrated pest management scheme to control Planococcus ficus, the vine mealybug, which occurs on all parts of grapevine, including the roots. When Steinernema yirgalemense was applied to the soil of two vineyards with P. ficus, contained in pierced Eppendorf tubes, buried at a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The commercial production of entomopathogenic nematodes as an environmentally safer option to the use of chemical insecticides can be regarded as being due to the increased understanding of their biology, and improved production methods and storage formulations (Friedman, 1990;Ehlers, 1996). According to Le Vieux and Malan (2013), such increased understanding and commercial production of EPNs are both pertinent in the pursuit of sustainable agriculture, and in helping to alleviate the global issues of species extinctions and ecosystem and biodiversity loss.…”
Section: Introductionmentioning
confidence: 99%
“…The commercial production of entomopathogenic nematodes as an environmentally safer option to the use of chemical insecticides can be regarded as being due to the increased understanding of their biology, and improved production methods and storage formulations (Friedman, 1990;Ehlers, 1996). According to Le Vieux and Malan (2013), such increased understanding and commercial production of EPNs are both pertinent in the pursuit of sustainable agriculture, and in helping to alleviate the global issues of species extinctions and ecosystem and biodiversity loss.…”
Section: Introductionmentioning
confidence: 99%
“…When S. yirgalemense was applied to the soil of two vineyards together with P. ficus, contained in pierced Eppendorf tubes, and buried at a depth of 15 cm in the soil, mortalities of up to 50 % were obtained after 48 h (Le Vieux & Malan, 2014). The persistence of S. yirgalemense, measured using codling moth larval mortality, was found to be zero in one vineyard, whereas, in another vineyard, it was 70 %, 12 weeks after application.…”
Section: Mealybugs (Pseudococcidae) In Deciduous Fruit Citrus and Grmentioning
confidence: 99%
“…The persistence of S. yirgalemense, measured using codling moth larval mortality, was found to be zero in one vineyard, whereas, in another vineyard, it was 70 %, 12 weeks after application. Tests were conducted to establish the production of scavenger-deterrent factors (Le Vieux & Malan, 2015) by H. zealandica and S. yirgalemense. Of the cadavers that were presented 6 days after nematode infection, 49 % of the H. zealandica, and 60 % of the S. yirgalemense infected cadavers were left intact.…”
Section: Mealybugs (Pseudococcidae) In Deciduous Fruit Citrus and Grmentioning
confidence: 99%
See 1 more Smart Citation
“…Two indigenous species, H. zealandica and S. yirgalemense, proved to be the most effective. Later research by Le Vieux and Malan (2015) indicated that S. yirgalemense was capable of detecting P. ficus individuals and actively seeking out mealybug hosts to infect.…”
Section: Introductionmentioning
confidence: 99%